2011
DOI: 10.1130/b30202.1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonostratigraphy of the Lesser Himalaya of Bhutan: Implications for the along-strike stratigraphic continuity of the northern Indian margin

Abstract: New mapping in eastern Bhutan, in conjunction with U-Pb detrital zircon and δ 13 C data, defi nes Lesser Himalayan tectonostratigraphy. The Daling-Shumar Group, 2-6 km of quartzite (Shumar Formation) overlain by 3 km of schist (Daling Formation), contains ~1.8-1.9 Ga intrusive orthogneiss bodies and youngest detrital zircon peaks, indicating a Paleoproterozoic deposition age. The Jaishidanda Formation, 0.5-1.7 km of garnet-biotite schist and quartzite, stratigraphically overlies the Daling Formation beneath th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 101 publications
5
144
0
Order By: Relevance
“…After adding the modern width of Greater India (i.e., the Himalaya, approximately 250 km N-S), these data suggest that Greater India in early Cretaceous time was not larger than approximately 900 km (SI Text). This conclusion is consistent with pre-Cretaceous Gondwana plate reconstructions (17,27) as well as with the notion that the Paleozoic and older stratigraphies of the Himalayan zones are correlative, suggesting that during their deposition Greater India formed a contiguous continental margin (16,(24)(25)(26). By assuming that Greater India remained only several hundreds of kilometers wide until collision with Asia, Aitchison et al (13,28) demonstrated that the leading edge of Greater India would have passed the equator approximately 55 Ma ago, and suggested that the 55-50 Ma collision record (what is widely regarded as the Tibetan Himalaya-Asia collision) resulted from just the obduction of ophiolites onto the leading, Tibetan-Himalayan edge of Greater India.…”
Section: Size Of Greater India Through Timesupporting
confidence: 85%
See 1 more Smart Citation
“…After adding the modern width of Greater India (i.e., the Himalaya, approximately 250 km N-S), these data suggest that Greater India in early Cretaceous time was not larger than approximately 900 km (SI Text). This conclusion is consistent with pre-Cretaceous Gondwana plate reconstructions (17,27) as well as with the notion that the Paleozoic and older stratigraphies of the Himalayan zones are correlative, suggesting that during their deposition Greater India formed a contiguous continental margin (16,(24)(25)(26). By assuming that Greater India remained only several hundreds of kilometers wide until collision with Asia, Aitchison et al (13,28) demonstrated that the leading edge of Greater India would have passed the equator approximately 55 Ma ago, and suggested that the 55-50 Ma collision record (what is widely regarded as the Tibetan Himalaya-Asia collision) resulted from just the obduction of ophiolites onto the leading, Tibetan-Himalayan edge of Greater India.…”
Section: Size Of Greater India Through Timesupporting
confidence: 85%
“…The amount of shortening accommodated within or below the Greater Himalaya prior to the Miocene therefore remains geologically unconstrained, but could be considerable. Detrital zircon studies of the Lesser, Greater, and Tibetan Himalaya suggest that their Neoproterozoic to lower Paleozoic (Cambrian-Ordovician) stratigraphies are similar (16,(24)(25)(26), suggesting that the net effect of post-Ordovician tectonics within the Himalaya was limited to perhaps several hundreds of kilometers of shortening.…”
mentioning
confidence: 99%
“…However, uncertainty remains 5 regarding the magnitude and age of slip along the KT. Long et al, (2011a) argued for 31-53 km of minimum KT displacement. We tested three kinematic scenarios in the flexural models by varying the relative timing of KT motion, called the Early KT, Split KT, and Late KT models (Fig.…”
Section: Kinematic Variations Consideredmentioning
confidence: 99%
“…The Lesser Himalayan zone consists of a package of Neoproterozoic to Permian strata, collectively grouped as the Upper Lesser Himalaya, and a suite of Paleoproterozoic strata comprising the Lower Lesser Himalaya (Long et al, 2011a).…”
Section: Tectonostratigraphymentioning
confidence: 99%
“…The Lesser Himalayan zone consists of Neoproterozoic to Permian strata, collectively grouped as the upper Lesser Himalaya, and Paleoproterozoic strata comprising the lower Lesser Himalaya (Gansser, 1983;Bhargava, 1995;Long et al, 2011a). The youngest unit of the upper Lesser Himalaya, the Permian Gondwana succession, is exposed north of the Subhimalayan zone in the hanging wall of the Main Boundary Thrust (MBT) and in the immediate footwall of the thrust sheet carrying the stratigraphically older Permian Diuri Formation.…”
Section: Tectonostratigraphymentioning
confidence: 99%